Examining the Multimodal and Multilingual Practices of Finnish Social Media Influencers - Limatius, Hanna (Routledge, 2023)
This chapter presents a qualitative study on the roles of multimodality and multilingualism in the online activities of Finnish social media influencers who create beauty- and fashion-focused content. Specifically, I analyse the ways in which these influencers utilise a combination of visual and linguistic representations on their social media, as well as the ways in which they combine the use of Finnish and English. The empirical analysis illustrates that there is variation in the multilingual practices that influencers utilise on different platforms, and that the use of these practices appears to change over time. The influencers also display a range of creative, multimodal practices that help them create and maintain a coherent brand across different social media channels.
Keywords: fi=Viestintätieteet|en=Communication Studies|